2017
DOI: 10.1111/myc.12615
|View full text |Cite
|
Sign up to set email alerts
|

The impact of real life treatment strategies for Candida peritonitis—A retrospective analysis

Abstract: Candida species are commonly detected isolates from abdominal foci. The question remains as to who would benefit from early empiric treatment in cases of Candida peritonitis. This study collected real-life data on critically ill patients with Candida peritonitis to estimate the relevance of the chosen treatment strategy on the outcome of these patients. One hundred and thirty-seven surgical intensive care unit (ICU) patients with intra-abdominal invasive Candidiasis were included in the study. Fifty-six patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It remains uncertain whether antifungal therapy would decrease the mortality rate associated with spontaneous peritonitis caused by fungi [23]. Previous studies suggest that directed antifungal therapy may not improve the outcomes of some patients with SFP [19,22], and this is partly attributed to the previous administration of empirical treatment for SBP and delays in initiating antifungal therapy [22].…”
Section: Discussionmentioning
confidence: 99%
“…It remains uncertain whether antifungal therapy would decrease the mortality rate associated with spontaneous peritonitis caused by fungi [23]. Previous studies suggest that directed antifungal therapy may not improve the outcomes of some patients with SFP [19,22], and this is partly attributed to the previous administration of empirical treatment for SBP and delays in initiating antifungal therapy [22].…”
Section: Discussionmentioning
confidence: 99%
“…isolation from peritoneal fluid was identified as a risk factor for mortality [ 25 ]. Mortality of IAC may exceed 50% [ 26 ], regardless that the introduction of echinocandins in the early 2000s was an important advance in managing invasive fungal infections [ 27 ]. The occurrence of non-bloodstream invasive candidiasis has increased in the last decade [ 28 ], with epidemiological data showing a progressive transition from C. albicans to non- albicans Candida species as etiological agents [ 29 ].…”
Section: Intraabdominal Candidiasis (Iac)mentioning
confidence: 99%
“…are determining factors for the outcome. A recent study analysing the real-life management of this entity showed that not all patients with Candida peritonitis received antifungal treatment in real clinical practice [ 26 ]. This review does not intend to analyse when antifungal treatment should be initiated based on the risk factors for invasive candidiasis or diagnostic methods, as have been addressed in other published articles [ 3 , 11 , 35 , 36 ].…”
Section: Pk/pd Principles For Optimisation Of Iac Treatmentmentioning
confidence: 99%
“…Although it remains uncertain whether antifungal therapies would decrease the mortality rate associated with spontaneous peritonitis by fungi [14,30,40], early initiation of antifungal therapies is necessary in SFP or suspected SFP cases. However, the questionwhen to start antifungal treatments-remains unanswered partly because of very low-quality of available evidence [4].…”
Section: Treatments For Sfpmentioning
confidence: 99%